Comparative assessment of critical quality attributes of sildenafil tablets - Brevedan, Marta Ingrid Victoria (2021)
Sildenafil citrate is a selective inhibitor of the enzyme phosphodiesterase type 5, used to treat erectile dysfunction in adults and pulmonary hypertension, mainly in children. This work aimed to perform a comparative study of sildenafil tablets marketed in Argentina and establish their pharmaceutical equivalence. Eight commercial formulations (immediate-release tablets) containing 50 mg of sildenafil were analyzed according to United States and Argentinian Pharmacopoeial guidelines. The assay was performed by UV spectrophotometry in 0.01 N hydrochloric acid. Similar conditions were used for dissolution tests, which were carried out in a basket apparatus at 100 rpm. All samples met pharmacopeial specifications for acceptance (i.e., assay, content uniformity, hardness, friability, disintegration, and in vitro dissolution) for immediate-release dosage forms. When compared to the reference formulation, a statistically significant difference was noted for dissolution efficiency in one case (sample F). Based on the obtained results, it is possible to conclude that the evaluated formulations of sildenafil can be considered pharmaceutical equivalents.